Development of a semantic search method for retrieving food related verses & concepts from the holy Quran using ontology - Rahman, Mohammed Mahmudur (IIUC Studies, 2022)
Qur’an is Allah (SWT)’s greatest miracle and is the source of all knowledge and information. As a Muslim, obligation is not only to recite the Qur’an but also it is important to gain knowledge from the Qur’an. Ontology is the best way to retrieve Quranic knowledge in a technical way. With the help of internet many search engines are found to discover information from Qur’an. But most of the search engines or information retrieval systems are keyword-based which can often lead to irrelevant results. To overcome this problem, semantic search is most useful in this case. The aim of research is to develop an ontological semantic based method to retrieve the food related verses and concepts from holy Qur’an by using natural language query. In this work, triplet extraction algorithm has been used for generating triple, the protege OWL editor 4.3 version used to create food ontology and the SPARQL Apache Jena fuseki server was used for querying. Quranic data are collected from English translation of the holy Qur’an. IIUC Studies Vol.18, December 2021: 101-122